PROBLEMS WITH THE 2013 CURRICULUM CHANGE ON THE QUALITY OF TEACHER TEACHING - Wahyu Pramesti; Mauliddhina Imas Permatasari; Muhamad Chamdani (Universitas Sebelas Maret, 2018)
Curriculum always develops following the current times. the change of curriculum implementation encountered many obstacles both from schools, teachers and students. . This research is a qualitative descriptive study. Data collection techniques used are questionnaires. this research aims to identify the problems of teachers in implementing the 2013 curricullum learning in elementary schools. this research is expected can give useful information about the 2013 curriculum problem on how the way the teacher teaches to improve the teaching learning qualityThe results of the study show that the problems of teachers come from the government, teachers, and students. The problems of the teacher include learning media, learning materials, learning methods, and the integration of the lessons learned in thematic learning. Students' problems are adaptation to thematic learning in the 2013 curriculum. The conclusion is that the implementation of the 2013 curriculum with good teacher quality can improve learning in school.